2014
DOI: 10.1155/2014/238724
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial-Temporal ARMA Model of the Incidence of Hand, Foot, and Mouth Disease in Wenzhou, China

Abstract: To investigate the variability of HFMD in each county of Wenzhou, a spatial-temporal ARMA model is presented, and a general Bayesian framework is given for parameter estimation. The proposed model has two advantages: (i) allowing time series to be correlated, thus it can describe the series both spatially and temporally; (ii) implementing forecast easily. Based on the HFMD data in Wenzhou, we find that HFMD had positive spatial autocorrelation and the incidence seasonal peak was between May and July. In the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…The age distribution of HFMD cases in Asia, compiled from a variety of sources including surveillance and cohort data, is summarized in Figure 5. Data from China [12][13][14]34,[49][50][51][52]94,[100][101][102][103][105][106][107] and Taiwan 5,6,73,108-111 are particularly abundant. Other sources include Hong Kong, 17,18 India, 76,80 Japan, 56,112 Korea, 54,95 Malaysia, 84,113 Singapore, 4,27,88 Thailand 22,23 and Vietnam.…”
Section: Age Distribution Of Hfmd Casesmentioning
confidence: 99%
“…The age distribution of HFMD cases in Asia, compiled from a variety of sources including surveillance and cohort data, is summarized in Figure 5. Data from China [12][13][14]34,[49][50][51][52]94,[100][101][102][103][105][106][107] and Taiwan 5,6,73,108-111 are particularly abundant. Other sources include Hong Kong, 17,18 India, 76,80 Japan, 56,112 Korea, 54,95 Malaysia, 84,113 Singapore, 4,27,88 Thailand 22,23 and Vietnam.…”
Section: Age Distribution Of Hfmd Casesmentioning
confidence: 99%
“…Similar to that in [5], we can obtain the threshold dynamics of model (1) as follows. Figure 1: e specific geography location of Wenzhou city, including 10 districts' county-level cities/counties [6].…”
Section: Dynamic Model Of Hfmdmentioning
confidence: 99%
“…In addition, Li et al [6] found that the distribution of HFMD in Wenzhou is heterogeneous at county level and Ouhai municipal district is the most severe region, followed by Lucheng, Longwan, and Ruian. For the sake of learning of HFMD dynamics in Wenzhou, we show the numerical results of 10 districts' county-level cities or counties in Figure 4.…”
Section: Parameter Estimation and Numerical Simulationsmentioning
confidence: 99%
See 2 more Smart Citations